Historical Tourism Opportunities In Muzrabad, Surkhandarya Region (Texas Journal of Multidisciplinary Studies, 2021)
Geography of Muzrabad district, historical tourism opportunities in muzrabad district, surkhandarya region, tourism opportunities of historical monuments of Muzrabad district were considered.